2014
DOI: 10.1116/1.4873689
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Bi and Se surface terminations of cleaved Bi2Se3 single crystals

Abstract: Evidence for the coexistence of both Bi and Se terminations of the topological insulator Bi2Se3 is presented that is connected with details of sample storage and cleaving procedures. X-ray photoelectron spectroscopy of the Bi 4f core levels show a lower binding energy component indicative of metallic Bi near the sample surface. Single crystals stored and cleaved in high vacuum predominantly show the usual Se surface termination while those stored in air for long periods of time have a high probability for Bi t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…The Bi-Bi metallic bonds that were sometimes observed following ex situ cleaving in refs. [9,15] were not detected. This is not unexpected, however, considering that the probability for an ex situ cleaved sample to be Bi-rich is small and there were only three trials in which XPS spectra were collected here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bi-Bi metallic bonds that were sometimes observed following ex situ cleaving in refs. [9,15] were not detected. This is not unexpected, however, considering that the probability for an ex situ cleaved sample to be Bi-rich is small and there were only three trials in which XPS spectra were collected here.…”
Section: Resultsmentioning
confidence: 99%
“…An intact QL would be terminated with Se atoms and have Bi in the second layer. Such a Se-termination has been widely demonstrated for samples cleaved in situ under vacuum [9][10][11]. A previous study from our group had found a Bi-termination, however, and included density functional theory (DFT) calculations which showed that termination by a complete Bi bilayer is energetically more favorable than the Se-termination [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The QLs are held together by a weak van der Waals force, so that Bi 2 Se 3 is expected to naturally cleave between QL's to reveal a Se-terminated surface. There are, however, different terminations reported in the literature following cleaving, including Se-termination [6][7][8][9], Bi-termination [10,11], oxidized surface [11,12], coexisting Seand Bi-terminations, either Se-termination or Bi-rich surfaces [6], and evolving surfaces [11].…”
Section: Introductionmentioning
confidence: 99%
“…An energetically favored heterostructure, Bi2Se3 (1×1)/Ag (1×1), with the selenium termination is adopted [37][38][39]. The ion-electron, electron-electron and van der Waals (vdW) interactions between Ag and Bi2Se3 are included in our model implemented in the Vienna ab initio simulation package (VASP) [24,40,41].…”
mentioning
confidence: 99%